How Community Pharmacists Perceive Ethics in Clinical Research: A Qualitative Study - Miku Ogura (MDPI AG, 2021)
In recent years, the importance of building evidence in clinical practice that is increasingly acknowledged globally has been recognized in Japan as well, and it is expected that clinical research by community pharmacists will grow. In Japan, however, community pharmacists have few opportunities to learn about research ethics and may lack the training to make ethical decisions. We conducted a questionnaire survey of community pharmacists (n = 200) using a free descriptive format to understand how they perceived research ethics. Our qualitative analysis of 170 respondents revealed various perspectives (<A pharmacist’s grounding>, <How pharmacists perceive research>, and <Ethical issues entailed by research>) of Japanese pharmacists on ethics in the context of clinical research. With respect to how to understand research, the following perspectives were found: “research that prioritizes researchers,” “research that prioritizes research subjects (patients),” and “research that enters into regular work.” The perspectives on “research that prioritizes research subjects (patients)” and “research that enters into regular work” may inadvertently lead to ethically inappropriate research due to mismatch in professional values or poor understanding of research. These findings can contribute to the development of an educational program for community pharmacists on research ethics.